Synthesis and biological evaluation of a series of analogues of 2,4,6-trihydroxy-3-geranylacetophenone, an anti-inflammatory natural product compound - Ng, Chean Hui (2017)
The natural product molecule 2,4,6-trihydroxy-3-geranylacetophenone (tHGA) isolated from the medicinal plant Melicope ptelefolia was shown to exhibit potent lipoxygenase (LOX) inhibitory activity. It is known that LOX plays an important role in inflammatory response as it catalyzes the oxidation of unsaturated fatty acids, such as linoleic acid to form hydroperoxides that are potent proinflammatory mediators. The search for selective LOX inhibitors may provide new therapeutic approach for inflammatory diseases. Previous studies reported that tHGA was an effective LOX inhibitor and was able to control airway-hyper-responsiveness in an acute model of murine asthma. However, the structure-activity relationship (SAR) of this group of compounds is still unknown. Herein, we report the synthesis of tHGA analogues using simple Friedel-Craft acylation, direct C-alkylation and methylation reactions with the objective of obtaining a better insight into the structure-activity relationships of the compounds. A total of seventeen synthetic analogues of tHGA were synthesized and evaluated for their soybean 15-LOX inhibitory activity, while three of them are new compounds. Modifications were made on the acyl moiety, alkyl moiety, and also the important hydroxyl group of phloroglucinol structural core. The combination of both electrophilic substitution on the phloroglucinol compound and nucleophilic substitution on the acylphloroglucinol derivatives gave tHGA analogues. In vitro soybean 15-LOX inhibiting activity was measured using spectrophotometric method. All the synthesized analogues showed potent to moderate soybean 15-LOX inhibitory activity in a dose-dependent manner (IC50 = 10.31–95.38 μM), the most active being compound 18e (IC50 value of 10.31 μM ± 1.5) with the longest aliphatic chain on the acyl substituent. Interestingly, four target compounds 18c (IC50 value of 12.32 μM ± 0.6), 18d (IC50 value of 15.26 μM ± 0.5), 18e (IC50 value of 10.31 μM ± 1.5) and 18g (IC50 value of 15.20 μM ± 1.2) exhibited better 15-LOX inhibition than tHGA (8) where improvement in activities range from approximately 30-50%. The SAR study revealed that the presence of a short, branched acyl substituent and the introduction of a cyclohexyl ring were less favourable for LOX inhibitory activity when compared to aliphatic acyl substituent. On the other hand, the introduction of a planar aromatic ring in the acyl substituent was found to improve the inhibitory activity. The results of the simple SAR study suggest that a longer, aliphatic and aromatic acyl substituent is favourable for better inhibitory action. Kinetic inhibition assay showed that both of the most active compound 18e and tHGA (8) are competitive inhibitors. Molecular docking studies (cDOCKER) and molecular dynamic (MD) simulation (GROMACs) revealed that hydrophobic interactions were the main driving force for the binding interactions of the active analogues with the target protein. Analogues with the larger lipophilic nature had better binding affinity as compared to others. Besides, the binding interaction with one crucial amino acid residue (His499) involved in iron chelation for the target enzyme correlates well with the kinetic assay’s result. Therefore, our findings support that these geranylated acylphloroglucinol compounds have promising potential as lead compounds for the design of new anti-inflammatory drugs or Non-Steroidal Anti-inflammatory Drugs (NSAIDs). The combination of both the bioassay results and in silico studies has reinforced the crucial structural features that are involved in the inhibitory activity which is important information for structure-based drug design.